IMPLEMENTASI COOPERATIVE LEARNING TYPE STAD (STUDENT TEAMS ACHIEVEMENT DIVISION) DALAM MENINGKATKAN PRESTASI BELAJAR MATEMATIKA - Pramonoadi, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2010)
The aims of this study is to improve learning process and increase learning outcomes for student  SMP Negeri 1 Bojonegoro class 2B, as much as 39 students. Increasing of learning outcomes  regarding both the average value of students as well as measured by the thoroughness standards of student learning. In the last round has been thoroughly studied all students with an average grade 76.4. The results of each cycle  learning outcomes has increased, in cycle I learning outcomes 74.36% with an average value of 69.7, cycle II 94.36% with an average value of 74.5, cycle at 100% with the value average of 76.4 and at post-test 100% with an average value of 80.2. This result show that   STAD cooperative learning on the subject of the relation mapping and graphics can improve student learning outcome. Implemtation of STAD cooperative learning from the cycle I, II, and III is crease. In the cycle I get 70.50%, of learning management; cycle II 80.59% and the cycle III 95.26%. Based on the results it can be said that teachers in managing learning are very good, because the teacher was trying to condition and direct the activities of students that are in teaching and learning activities.